From Peril to Protection: an evaluation of regulations impacting eScooter injuries - Leslie M Kobayashi; Todd W Costantini; Jay J Doucet; Jarrett E Santorelli; Laura N Haines; Kendra M Black (Trauma Surgery & Acute Care Open)
Background The use of standing electric motorized scooters (eScooters) has skyrocketed since its first release in 2016. This quickly popularized form of transportation has been associated with significant injury and even death. These eScooter-related traumatic injuries led to local advocacy efforts, resulting in safety restrictions including speed limit geofencing, sidewalk restrictions, and limiting the number of eScooter providers in high-density population areas. We hypothesized that these local safety restrictions decreased the number of eScooter-related injuries presenting to our trauma center. Methods This is a retrospective cohort study of eScooter-crash patients presenting to our Level 1 trauma center from July 2018 to June 2023. Variables included patient demographics, injury severity score (ISS), and mortality. The primary outcome was the rate of eScooter patients presenting over time in relation to the implementation of local-regional safety regulations.Results A total of 381 patients presented after eScooter crashes. Males were 73.8% of patients. The average age was 38.6 years; 45+ years was the most common age group at 33%, followed by ages 25–34 (31%). The mean ISS was 9±6, with ISS 0–9 (65.1%), 10–15 (24.4%), 16–24 (8.4%), and >25 (20.1%). There were three (0.8%) deaths. The median number of eScooter patients per month with prespeed limits was nine and post five (p=0.005), showing a 44.4% decrease in injured patients. After February 2022 restrictions, the rate precipitously declined with a median of two (p=0.033), reflecting an additional 60% decrease in injured patients.Conclusion Local advocacy resulting in increased safety regulations was associated with a significant reduction in injured patients secondary to eScooter use. This demonstrates the importance of advocacy efforts in response to changes in injury patterns and mechanisms of injury. We believe that our work can serve as a model for other urban centers seeking to reduce eScooter-related injuries and implement effective safety measures.Level of evidence IV, prognostic/epidemiologic.